Systematic Analysis Strategy Based on Network Pharmacology to Investigate the Potential Mechanism of Fritillaria thunbergii Miq. against Idiopathic Pulmonary Fibrosis. (28th November 2022) - Xu, Gonghao; Feng, Siwen; Sun, Rui; Ding, Qi; Shi, Yuanyuan
Abstract : Idiopathic pulmonary fibrosis (IPF) is a long-term, distressing, and age-related interstitial lung disease characterized by a complicated etiology and irreversible progression. Fritillaria thunbergii Miq. (Zhe Beimu, ZBM) is frequently used for its heat-clearing and phlegm-resolving properties in herbal compounds for the treatment of IPF. However, the specific mechanisms underlying the effects of ZBM against IPF have not yet been reported. In this study, we applied a systematic analysis strategy based on network pharmacology to explore the probable core targets and major pathways of ZBM against IPF. In addition, molecular docking simulation and quantitative real-time polymerase chain reaction (qRT-PCR) were performed to preliminarily investigate the possible mechanisms underlying the therapeutic effects of ZBM on IPF. We collected a total of 86 components of ZBM and used network pharmacology analysis to screen nine presumptive targets of ZBM against IPF. The molecular-docking results indicated that the components of ZBM exhibited good binding activity with presumptive targets. The qRT-PCR results also suggested that ZBM may partly alleviate IPF by regulating the expression of presumptive targets. This study laid the foundation for further clinical applications of ZBM and the development of IPF-related therapeutic products.